The Establishment of Segmented Constitutive Relationship of Coal under Triaxial Compression: Take the No. 3 Coal of Xinhe Colliery as an Example - Yongjie Yang; Yang Zhang; Tianli Zhang (Advances in Civil Engineering)
Constitutive relationship of coal under triaxial compression must be determined during solving the theoretical calculation and numerical simulation about coal body failure. This paper carried out the conventional triaxial compression test on No. 3 coal of Xinhe Colliery using the MTS815.03 servo-controlled rock mechanical test system. The results indicate that the failure process of coal can be divided into 5 stages: densification stage, apparent linear elastic deformation stage, accelerated inelastic deformation stage, fracture and developing stage, and plasticity flow stage. Within the test confining pressure (20 MPa), the peak strain of coal is approximately linearly positively correlated with the confining pressure. The relationship between elastic modulus of coal and confining pressure is quadratic polynomial. The triaxial compressive strength and residual strength of coal are approximately linearly positively correlated with confining pressure. The constitutive relationship model of coal can be simplified as the four segments of straight line model of “elastic–plastic hardening–plastic softening–residual perfectly plastic.” Through fitting calculation of test data, the segmented constitutive equation of coal can be obtained, and the every segment span of strain.